Implementasi Norma Hukum Terhadap Tindak Pidana Peretasan (Hacking) di Indonesia - Azzahra Mazaya Khalisah; Putri Kirana (Faculty of Law, Universitas Airlangga, 2022)
AbstractCybercrime is a crime related to technology or cyberspace against public or private interests. Act Number 11 of 2009 concerning Information and Electronic Transactions as amended in Act Number 19 of 2019 (hereinafter referred to as UU ITE) regulates cybercrime in 9 main articles, one of which is the crime of hacking. Further investigation with cases that emerged in the last 2 years such as Hacking WhatsApp Accounts from 8 ICW Coordinators to hacking Ganjar Pranowo's Youtube account. However, Indonesian legal norms governing cybercrimes are still limited to the UU ITE. Increasing internet accessibility in Indonesia has not been harmonized with law enforcement and even faces serious issues in society. Thus, the purpose of this paper is to analyze the preventive or repressive aspects of the criminal act of hacking, the preparation of Indonesian criminal law in dealing with cybercrimes, and the punishment of criminal acts using the normative analysis method. Keywords: Hacking; Cybercrime; Crime. AbstrakKejahatan Siber atau Cybercrime merupakan tindak pidana atau kejahatan yang berkaitan dengan teknologi atau cyberspace terhadap kepentingan umum maupun kepentingan pribadi. Undang-Undang Nomor 11 Tahun 2009 tentang Informasi dan Transaksi Elektronik sebagaimana telah diubah dalam Undang-Undang Nomor 19 Tahun 2019 (selanjutnya disebut sebagai UU ITE) mengatur tindak pidana cybercrime dalam 9 pasal utama, salah satunya adalah tindak pidana peretasan atau hacking. Menelisik lebih lanjut dengan adanya kasus yang muncul 2 tahun terakhir seperti Peretasan Akun Whatsapp dari 8 Koordinator ICW hingga peretasan akun Youtube Ganjar Pranowo. Akan tetapi, norma hukum Indonesia yang mengatur terkait kejahatan siber masih terbatas pada UU ITE. Peningkatan aksesibilitas internet di Indonesia belum diselaraskan dengan penegakan hukum bahkan menghadapi isu serius di masyarakat. Dengan demikian, tujuan dari penulisan ini adalah menganalisa aspek preventif ataupun represif tindak pidana peretasan, persiapan hukum pidana Indonesia dalam menangani kejahatan siber, dan pemidanaan dari tindak pidana menggunakan metode analisa normatif.Kata Kunci: Hacking; Kejahatan Siber; Tindak Pidana.